New Cretaceous lungi sh material from southern South America, Argentina - Giordano, Paula Guillermina (2017)
Dipnoi is a large group of sarcopterygians which ranges from the Early Devonian to thepresent. Traditionally, it was considered that their taxonomic diversity decreased at the end ofPaleozoic. Dipnoans are abundant in the fossil record and their preservation state varies. The materialstudy herein was collected in La Invernada locality, at 50 km southwest from the Rincón de losSauces city, Neuquén Province, Argentina. We present the i rst dipnoan skull record from the Mesozoicof South America and gives a preliminary description of the material. The new specimens have beenidentii ed as a Ceratodontidae indet.